Characterization and ionic conductivity of polymeric electrolytes based on chitosan-ammonium thiocyanate- tiOz ceramic materials - Aziz, N.A. (2009)
Various amounts of Ti02 particles are used as filler in preparation of chitosan-ammonif thiocyanate-composite polymer electrolytes. The role of filler in this present work is as 8 agent to improve the conductivity of the films. Films of chitosan and its complexes were prepared using solution casting technique. Different amounts of Ti02 3 wt. %, 6 wt. %, 9 wt. %, 12 wt. %, 15 wt. % and 18 wt. % were added to the highest room temperature conducting sample in chitosan-salt system i.e sample containing 40 wt. % NH4SCN. The impedance ( the composite films has been measured in the temperature and the frequency range 298 K to 373 K and 50 Hz to 1 MHz, respectively. The conductivity value of this sample is 1.29 x IJ Scm-I. With addition of 3 wt. % Ti02 filler the ionic conductivity increased to 2.75 x 10-4 S cm-1. XRD and FTIR results are also disscused.